Quantum Phase Properties: Quantum Phase Properties of Photon Added and Subtracted Displaced Fock States (Ann. Phys. 11/2019). Issue 11 (11th November 2019) - Malpani, Priya; Thapliyal, Kishore; Alam, Nasir; Pathak, Anirban; Narayanan, Venkatakrishnan; Banerjee, Subhashish
Abstract : In article 1900141, Priya Malpani, Anirban Pathak, and co‐workers studied different aspects of quantum phase properties of a set of engineered quantum states, which can be reduced from photon added/subtracted displaced Fock state, in view of their applications in quantum technology. This image represents the polar plot for quantum phase distribution of this set of engineered quantum states.